CHEMICAL-BASED INSPIRATIONAL THEORETICALLY LABORATORY EXPERIMENTAL TREATMENTS FOR SUGAR-MALABSORPTION DISEASES. - Azzam, Ahmed Y. (Journal of Biomedical and Pharmaceutical Research, 2019)
The process of glucose absorption inside the body is initiated in stomach like any type of micro-chemical nutrients but specially in , epithelial cells lining small intestine. though Na+/glucose cotransporter (SGLT1) electrochemically, other transporters and sometimes using intestinal polypeptides involved. Dysfunction of epithelial cells of small intestine, transporters or in malignant cases in, absorption intestinal polypeptides leads to a rare disease called Glucose-galactose malabsorption. In this disease absorption of sugar molecules is not done probably it’s accompanied baby born genetic disease. Which leads to precipitation of large sugar molecules not absorbed. In other disease that called Hypochlorhydria. Which is lack of HCl production due Pernicious anemia, surgical operations in digestive system, H.Pylori, gastric bypass, VIPomas, Hypothyroidism, Radiations to GIT system and gastric cancer could lead to production of very small amounts of HCl which also in some cases ( Not All ) has effect on absorption of sugar from gastric fluid. In this publication I’ll focus more on Hypochlorhydria sugar-malabsorption side-effect in some patients who may suffer from it. In the other hand, I’ll try to involve Glucose-galactose malabsorption disease but it will be limited in the experiments because, this disease is due to genetic mutations not due to gained pathological factors during life. In recent researches in highly accurate simulated chemistry lab in In-Vitro experiments to keep out from hazards reactions of real-life chemistry lab chemical medication experiments results . I’ve found that D-Gluconic acid when manufactured as sugar source instead of direct sugar has a very good effect for people who is suffering from sugar malabsorption caused of gastric fluid problems. It shown it’s better ability to get soluble easily in the gastric pathway and stomach fluid. Acetic acid and Calcium acetate shown that they have good effect for Hypochlorhydria patients with sugar. They help on faster sugar absorbing and establishing sugar bonds before getting absorbed which makes it easier to digest. On the other hand Aluminum high doses shown that it may be a struggling source for people who suffer from gastric fluid problems like Hypochlorhydria so it’s recommended to reduce and take care of taking doses of aluminum. For Glucose-galactose malabsorption disease patients. D-Gluconic acid can be used as a secondary-stabilizer disease reducer in addition to acetic acid for helping to break sugar bonds if the patient needed to get sugar source for emergency cases to make it easier for some mild cases to digest but, it can’t be used for long time because it’s not so much effective but it’s a disease partial reducer for emergency sugar needed cases. It shown that it may help in some of mild cases severe cases aren’t included yet in this experiment since it has no effect on them at most.